GENETIC ASPECTS OF MYOCARDIAL INFARCTION: PROBLEMS AND PERSPECTIVES - P. A. Shesternya; V. A. Shulman; S. Yu. Nikulina (Российский кардиологический журнал)
The role of hereditary factors in the development of coronary heart disease and myocardial infarction is known, but the underlying pathogenetic mechanisms remain understudied. Multiple studies of candidate genes (those coding protein synthesis, participating in atherosclerosis pathogenesis, or regulating hemostasis and inflammation) have not been particularly successful. The main problem of these studies has been a very low level of reproducibility of the results obtained. By contrast, whole-genome association studies have provided new perspectives in this research area. This review discusses the modern relevant evidence and new directions for future research.